Development of modified fractional fluid flow equation for non–darcy flow in computer simulation of oil reservoirs (2021)
Upon the depletion of oil reservoir, huge amount of oil is usually left behind. This oil, in some cases double the initial oil recovered, in order to recover the unrecovered oil, different types of secondary oil recovery techniques can be explored. A more common technique is water flooding which involve the injection of water into reservoir to displace oil into the wellbore. To determine the relative flow rates of oil and water at any point in a porous flow system while also examining factors such as fluid properties, rock properties, reservoir structural properties, pressure gradient, and flow rate which affect the displacement efficiency of a water flooding project, the fractional flow equation is employed. But the convectional fractional flow equation is applicable just to Darcy flow. The use of Darcy flow equation is not applicable in low permeability sandstone reservoir, hence non Darcy flow have been used one of such equation is the Forcheimer equation, as a result this study is aimed at modifying the Forcheimer equation and validating the new fractional flow equation using literature . The result obtained showed that the proposed equation predicts better than Forcheimer equation